IOT Based Agribot for Agricultural Farming - Hegde, Vasudha; M, Sumathi; Nagarajaiah, Varsha; MC, Yeshaswini; Raj BR, Prof. Chandan (International Journal of Computer Sciences and Engineering, 2025)
Every living being requires energy for which it depends on food. Human population rely on agriculture, one of the main sources of food. In this project the main focus is to aid agricultural activities using IOT techniques in an effective and user-friendly manner. The system here consists of an agricultural robot which performs grass cutting, ploughing, seeding along with obstacle detection. All these functions of Agribot is chosen using user-friendly mobile application. Agribot uses Renesas microcontroller, DC motors for wheel rotation, to rotate cutting blades, to open or close seeding valve and to move the ploughing arm. Ultrasonic sensor is used for obstacle detection and android app is the mobile application. Bluetooth module is used to communicate between the app and Agribot. The function selected by the user is also displayed on the LCD of the Agribot. Agribot thereby helps to increase profit margins of farmers with minimal investments.